Abundance, Species Diversity, and Distribution of Diurnal Mammals in Humbo Community-Based Forest Area, Southern Ethiopia - Lemma, Adanech; Tekalign, Wondimagegnehu (International Journal of Zoology, 2020)
This study was undertaken with the intention of assessing abundance, species diversity, and distribution of medium and large diurnal mammals at the Humbo Community Based Forest Area, Ethiopia. The study area was stratified into three major habitats based on the vegetation cover of the area, such as riverine forest, bushland, and open grassland. The study in each vegetation type was surveyed using the transect method. It was conducted on foot along a randomly selected transect line. A total of eight large and medium mammalian species were recorded. The species recorded were Papio anubis, Sylvicapra grimmia, Tragelaphus scriptus, Chlorocebus pygerythrus, Tragelaphus strepsiceros, Lepus fagani, Phacochorus ethiopicus, and Panthera leo. During the survey, the leading order recorded was Artiodactyla followed by Primates. In terms of relative abundance, Anubis baboon (28.4% and 28.1%) and common duiker (19.4% and 11.4%) were the most abundant species, while warthog (12.1% and 8.9%) and lion (0.7% and 0.4%) were the least abundant during the wet and dry seasons, respectively. The highest number of mammalian species were distributed in bushland habitat during both wet (n = 7) and dry (n = 7) seasons. The highest Shannon-winner diversity index and evenness were obtained in the bushland habitat (1.70 and 2.21) during wet and dry seasons, respectively. Though the forest is the living place for various wild mammalian species, the conservation measures of the local community should also consider those species in line with the efforts that have been done on forest management practices.